Medya’ da etik - Çalışkaner, Özlem (My University, 2002)
The first part of the thesis brings explanations for the concepts of ETHICS and MORALS, which are complementary for, but easily confused with each other and therefore considered separately. Second part focuses on the historical development of the concept of ethics in Turkey and throughout the world. Rules of press ethics and auto-control in Turkey and various countries cover third part. Actual status for the issues of 'Characteristics of journalism and ethics' and 'journalism and social responsibility' have been mentioned in part four. This part presents clues about the difficulties and restrictions journalists encounter, while indicating the ethical infringements appearing throughout the media. The profession of journalism and the domain of media, hold an effective position in social arena. Ethical responsibility extends as the power gained and its capability to influence other people increase. Therefore the requirement for legal regulations, as for every social aspect, is also valid for press. Further, there are code of journalistic ethics and various auto-control and control mechanisms that bonds the professional effectiveness of every journalist to a certain professional ethics system. Besides professional press principles, examples can be listed as Press Honor Council, Council of Press, Top Committee of Radio and Television, implementation of ombudsmanship, and assessment of the press ethics through articles. Most of the self-assessment and supervision mechanisms mentioned above have practically failed due to ineffective sanctions like warnings, reproaches and exposures. The process of news publishing includes restrictions like time, visual aesthetics, overdone entertainment, economical issues, gatekeepers and censorship. The first prerequisite for the journalists and the media to conform to the ethical principles is the guarantee given for the economic and legal independence against the government and politics, of which Turkish media partially lacks. Secondly comes the minimum independence of the editorial affairs against the publishing house.
Keywords: Gazetecilik Türkiye; Medya